Women’s Costume of Inner Mongolia in Modern Chinese Easel Painting - Wang, Chong; Alforova, Zoya (HUDPROM: The Ukrainian Art and Design Journal, 2023)
The article is devoted to the peculiarities of the representation of the female costume of Inner Mongolia in modern Chinese easel painting. The purpose of the article is to understand the stylistic, compositional, and coloristic solutions of the mirroring of women’s costumes by Chinese easel makers at the end of the 20th – beginning of the 21st century. The administrative autonomy chosen for analysis is a fairly self-sufficient region of China, in which a peculiar complex of women’s costume was formed. Its representation in easel painting makes it possible to capture a certain picture of the world, specific to Inner Mongolia. The research methodology is based on the methods of general-theoretical, formal-stylistic and compositional-coloristic analysis of works of fine art. The author analyzes publications in which the state of Chinese and foreign scientific discourse on the specified problem is investigated. On the examples of the analysis of the paintings of Jin Gao, Chen Yifei, Chen Yanning and other modern easel painters, the artistic features of the representation of two versions of the female costume complexes of Inner Mongolia are revealed: ethnic and historical. It has been proven that the components of such a complex of women’s costumes were a robe with special elements (cuffs and linshui), a wide skirt (or pants) and boots made of soft leather. A special element of such a complex was the geometric ornament, the colors of which changed depending on the type of costume and the circumstances of its use. The analysis of the representation of both variants of the female costume complex proved that the ethnic variant is usually presented in a realistic style, in accordance with the canons of classical Chinese painting. Artists, as a rule, use fairly simple compositional solutions with both a single figure and a multi-figure plot. The color palette of such images is warm, ochre-brown, and the clothes depicted are usually contrasting (white, red, blue). All the mentioned means of artistic expression and pictorial techniques testify to the fact that modern Chinese easel artists strive to preserve the cultural heritage of the specified autonomous region.